Application of Intelligent Speech Synthesis Technology Assisted by Mobile Intelligent Terminal in Foreign Language Teaching. (21st May 2022) - Zhang, Zhehua
Abstract : In today's increasingly frequent international exchanges, language ability has been paid more and more attention. However, the current foreign language teaching in some areas lacks a standard external input environment, and the gap between learners' own ability and the new requirements has not been effectively solved. At present, intelligent speech synthesis technology is mature. It is found that this technology can play a unique advantage in language teaching. Based on this, this study studies the feasibility of the application of intelligent speech synthesis technology in foreign language teaching from the perspective of technology. On this basis, the application mode of intelligent speech synthesis technology in foreign language teaching is constructed to verify its application effect in foreign language teaching. The main research work of this paper is as follows: firstly, it analyzes the feasibility of using clever speech synthesis technologies to teach foreign languages, and it lists in detail the application conditions of intelligent speech synthesis technology in different teaching activities and course types. Then, it constructs the application mode of intelligent speech synthesis technology in foreign language teaching. Finally, the experimental research on the application mode of intelligent speech synthesis technology in listening teaching is carried out. The experimental results show that intelligent speech synthesis technology has achieved good results in foreign language teaching and laid a foundation for foreign language teaching research.